Study of Critical Thinking Skills for Junior High School Students In the Era Industial Revolution 4.0 - Azmi, Zahara Lutfiya; Marlina, Leni; Fathurohman, Apit; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Sari, Diah Kartika; Gustiningsih, Tria; Rawani, Dewi; Lisnani, Lisnani; Sari, Arika; Septimiranti, Delia (Universitas Nurul Huda, 2022)
The background of the research is that skills are needed in accordance with the era of the industrial revolution 4.0, especially in the 21st century, namely critical thinking skills. For this reason, research is needed to determine the description of critical thinking skills. This research is a preliminary study that aims to describe the ability of critical thinking skills in learning science physics. Descriptive research method using google form. The research subjects were 33 students of SMP Negeri 59 Palembang. The results obtained are 25% of students are able to focus questions, 30% analyze questions, 32% consider reliable sources or not, 17% observe, consider observation reports, 39% do and consider deduction results, 38% do and consider induction results, 42% make and determine the value of judgment, 25% define, consider definitions, 21% identify assumptions, 44% determine actions, and 54% interact with others. The description of the critical thinking skills of junior high school students in the 4.0 industrial revolution era Physics science material is still in the low category, judging by the percentage of student responses. Suggestions for further research on efforts that can overcome the low critical thinking skills of junior high school students on Physics Science material.